Well-defined survival outcome disparity across age cutoffs at 45 and 60 for medullary thyroid carcinoma: a long-term retrospective cohort study of 3601 patients - Zhang, Kun; Wang, Xinyi; Wei, Tao; Li, Zhihui; Zhu, Jingqiang; Chen, Ya-Wen (Frontiers in Endocrinology, 2024)
Background: Medullary thyroid cancer (MTC) is a challenging malignancy. The survival outcome of MTC based on AJCC staging system does not render a discriminant classifier among early stages.Methods: 3601 MTC patients from 2000 to 2018 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Smooth curve fitting, Cox proportional hazard regression and competing risk analysis were applied.Results: A linear correlation between age and log RR (relative risk of overall death) was detected.Overlaps were observed between K-M curves representing patients aged 45-50, 50-55, and 55-60. The study cohort was divided into 3 subgroups with 2 age cutoffs set at 45 and 60. Each further advanced age cutoff population resulted in a roughly "5%" increase in MTC-specific death risks and an approximately "3 times" increase in non-MTC-specific death risks.The survival outcome disparity across age cutoffs at 45 and 60 for MTC has been well defined.